2012
DOI: 10.1369/0022155412440001
|View full text |Cite
|
Sign up to set email alerts
|

Microdeletion and Microduplication Syndromes

Abstract: The widespread use of whole genome analysis based on array comparative genomic hybridization in diagnostics and research has led to a continuously growing number of microdeletion and microduplication syndromes (MMSs) connected to certain phenotypes. These MMSs also include increasing instances in which the critical region can be reciprocally deleted or duplicated. This review catalogues the currently known MMSs and the corresponding critical regions including phenotypic consequences. Besides the pathogenic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
102
1
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(116 citation statements)
references
References 30 publications
1
102
1
12
Order By: Relevance
“…13,15 For other disorders, deletions and duplications involving the same dosagesensitive genes result in significantly different clinical presentations, such as seen in Williams syndrome and chromosome 7q11.23 duplication syndrome. 13,16 From the current study, it appears that MBD5 falls into the former category of dosage-sensitive genes, but additional cases will need to be studied to determine if there are features which have not been identified or are underappreciated. The phenotypes observed in the microdeletion and microduplication syndrome are similar, with the 2q23.1 microduplication syndrome having a somewhat milder phenotype.…”
Section: Discussionmentioning
confidence: 95%
“…13,15 For other disorders, deletions and duplications involving the same dosagesensitive genes result in significantly different clinical presentations, such as seen in Williams syndrome and chromosome 7q11.23 duplication syndrome. 13,16 From the current study, it appears that MBD5 falls into the former category of dosage-sensitive genes, but additional cases will need to be studied to determine if there are features which have not been identified or are underappreciated. The phenotypes observed in the microdeletion and microduplication syndrome are similar, with the 2q23.1 microduplication syndrome having a somewhat milder phenotype.…”
Section: Discussionmentioning
confidence: 95%
“…It has been demonstrated that CNVs (i.e., deletions or duplications of chromosomal segments) have a strong relationship with genome variability and contiguous gene syndrome and might be responsible for several conditions associated with short stature [18]. In 2009, the American College of Medical Genetics published the first practice guideline for genetic evaluation of short stature, which includes the recommendation for CNV investigation in patients with proportional short stature and other physical or developmental defects with an unrecognized syndrome [4].…”
Section: Discussionmentioning
confidence: 99%
“…Patients carrying reciprocal microduplication at 5q35.2q35.3 have no clinical phenotype or have a milder phenotype than do patients with microdeletion of the same region (Kirchhoff et al, 2007;Weise et al, 2012). According to Orphanet Report Series (2016), the number of published cases of the 5q35 microduplication worldwide is 14.…”
Section: Introductionmentioning
confidence: 99%